2013
DOI: 10.3126/ijim.v2i3.8665
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of urinary tract infection among children attending Gandaki Medical College Teaching Hospital and Research Center, Pokhara, Nepal

Abstract: INTRODUCTION: Urinary tract infection (UTI) is considered as the most common bacterial infectious disease seen among the pediatric patients. Most commonly, members of Enterobacteriaceae, particularly uropathogenic strains of E. coli and Enterobacter spp. are the primary causative pathogens of UTI in the different part of the world. Emergence of antimicrobial resistance rates among pathogens recovered from urinary tract infections is an increasing problem in the specific region. MATERIALS AND METHODS: Prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Age-wise distribution showed that the highest prevalence of UTI was seen in children aged 0-5 years (39.2%). This agrees with the work of Rai et al that reported the highest prevalence among children less than six years but disagrees with the work of Gautam et al that reported the highest prevalence among 6-10 years [26,28]. The higher prevalence of UTI among 0-5 years in our work could be because younger children are not well toilet trained with the likelihood of ascending infection from fecal flora [28].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Age-wise distribution showed that the highest prevalence of UTI was seen in children aged 0-5 years (39.2%). This agrees with the work of Rai et al that reported the highest prevalence among children less than six years but disagrees with the work of Gautam et al that reported the highest prevalence among 6-10 years [26,28]. The higher prevalence of UTI among 0-5 years in our work could be because younger children are not well toilet trained with the likelihood of ascending infection from fecal flora [28].…”
Section: Discussionsupporting
confidence: 66%
“…On the contrary, Gautam et al reported high prevalence in males (51%) when compared to females (48%) with a ratio of 1:1.06. [26]. High prevalence of urinary tract infections (UTIs) in the female is as a result of many factors such as proximity of the female urethra to the anus, as well as incomplete and inordinate voiding of urine of schoolgirls of which is often associated with constipation and encourages infections of the urinary tract [27].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infection (UTI) is an infection in any part of urinary system (kidneys, ureters, bladder and urethra) ( 1 ). It is one of the commonest bacterial infections encountered in daily clinical practice and a major problem that is frequently encountered by pediatrics healthcare providers ( 2 , 3 ). It begins when uropathogens that reside in the gut contaminate the per-urethral area and /or through hematogenous spread, are able to colonize the urethra.…”
Section: Introductionmentioning
confidence: 99%